Aplikasi Pembelajaran Interaktif Sistem Peredaran Darah Manusia Untuk Kelas 5 Sekolah Dasar - Porsche, Devrico; Tulenan, Virginia; Sugiarso, Brave A. (Jurnal Teknik Informatika, 2019)
Abstract — Human cardiovascular system is a closed and double circulation system. At school, human cardiovascular system is one of fairly difficult topics to be understood by students. This is primarily caused by its complex learning material such as the organs and diseases, while the students can only access it from books. The learning media used are not maximal and are less effective. The idea is to develop an interactive learning application of human cardiovascular system using computer technology, which is designed for grade 5 students of elementary school. By using a more interesting learning aid, the objective is to increase students’ interest in learning, as well as their understanding of the subject matter. This application is a desktop-based program that uses ADDIE model. The stages of ADDIE model consist of analysis, design, development, implementation, and evaluation.  Keywords — ADDIE, Cardiovascular System, Desktop, Learning Ai.Abstrak — Sistem peredaran darah manusia adalah sistem peredaran darah tertutup dan ganda. Sistem peredaran darah pada manusia adalah salah satu materi yang cukup sulit untuk dipahami oleh siswa. Selain itu banyak materi seperti, alat peredaran darah, dan gangguan penyakit yang berbagai macam dirasakan sulit untuk dipahami jika hanya mendengarkan guru, dan juga membaca buku teks saja. Media pembelajaran yang digunakan tidak maksimal dan kurang efektif. Karena itu dirancanglah aplikasi media pembelajaran interaktif sistem peredaran darah manusia untuk kelas 5 sekolah dasar yang menarik, mampu meningkatkan minat siswa dan dapat membantu siswa untuk memahami materi sistem peredaran darah pada manusia. Aplikasi ini berbasis desktop dengan menggunakan metodologi pengembangan ADDIE. Tahapan pada metodologi ADDIE antara lain analisa (analysis), perancangan (design), pengembangan (development), implementasi (implementation), dan evaluasi (evaluation).  Kata kunci — ADDIE, Desktop, Media Pembelajaran, Sistem Peredaran Darah.